3D lithiophilic–lithiophobic–lithiophilic dual-gradient porous skeleton for highly stable lithium metal anode. Issue 1 (6th December 2019) - Zheng, Hongfei; Zhang, Qingfei; Chen, Qiulin; Xu, Wanjie; Xie, Qingshui; Cai, Yuxin; Ma, Yating; Qiao, Zhensong; Luo, Qing; Lin, Jie; Wang, Laisen; Qu, Baihua; et al.
Abstract : A 3D porous lithiophilic–lithiophobic–lithiophilic dual-gradient CAZPZ current collector is designed to regulate homogeneous Li deposition, and the CAZPZ–Li hybrid anode has superb practical applications in different full cells. Abstract : The lithium metal anode has been considered the most promising anode in rechargeable batteries to meet the ever-increasing requirements of high energy density. Herein, a 3D porous lithiophilic–lithiophobic–lithiophilic dual-gradient Cu–Au–ZnO–PAN–ZnO (CAZPZ) current collector is fabricated to suppress Li dendrite growth. The lithiophilic Au and ZnO at the bottom are favorable for homogeneous Li nucleation, the ZnO–PAN–ZnO skeleton provides plenty of space to accommodate deposited Li and the lithiated ZnO (Li2 O/Li x Zn) layer can act as an artificial SEI to regulate the well-distributed Li + flux. As a result, long-term stabilization for 1200 h at 0.5 mA cm −2 and a low overpotential of 22 mV at 3 mA cm −2 are achieved in symmetric cells. Moreover, the CAZPZ–Li hybrid anode exhibits superb electrochemical properties when matched with a LiFePO4 (LFP) cathode. The CAZPZ–Li‖LFP full cells exhibit excellent stabilization for 1000 cycles at 5C with a high capacity retention of 97.3%. The lithiophilic–lithiophobic–lithiophilic dual-gradient design of the 3D porous current collector for the Li metal anode can be a very promising strategy to enable the practical application of Li metal batteries.